2022
DOI: 10.1002/ange.202208660
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline Porous Organic Salt for Ultrarapid Adsorption/Desorption‐Based Atmospheric Water Harvesting by Dual Hydrogen Bond System

Abstract: In recent years, the porous sorbent-assisted atmospheric water harvesting (AWH) method has emerged as an effective approach for solving water crises without geographical restrictions. However, there is a limited array of porous adsorbent materials that can be used for AWH, which are inadequate to meet the needs under different climatic conditions. In light of this, herein, we synthesize a new crystalline porous organic salt (CPOS; denoted as CPOS-6) possessing a dual hydrogen bond system and verify its applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…11,12 Although researchers have incorporated hygroscopic salts into these materials to enhance their water adsorption capacity under ambient conditions, the strong affinity of hygroscopic salts for water molecules in turn leads to a reduced water release/production efficiency. 13,14 For example, Li et al reported a PAM-based hydrogel containing calcium chloride and carbon nanotubes with a maximum water adsorption capacity of 2.05 g g −1 and a low desorption efficiency of 55%. 15 The trade-off between water uptake (under low-mediate humidity) and water release efficiency under ambient conditions limits the practical applications of artificial AWH materials.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 Although researchers have incorporated hygroscopic salts into these materials to enhance their water adsorption capacity under ambient conditions, the strong affinity of hygroscopic salts for water molecules in turn leads to a reduced water release/production efficiency. 13,14 For example, Li et al reported a PAM-based hydrogel containing calcium chloride and carbon nanotubes with a maximum water adsorption capacity of 2.05 g g −1 and a low desorption efficiency of 55%. 15 The trade-off between water uptake (under low-mediate humidity) and water release efficiency under ambient conditions limits the practical applications of artificial AWH materials.…”
Section: ■ Introductionmentioning
confidence: 99%
“…At night, the tip of the spike array can liquefy the water vapor in the air, and the liquefied water droplets can gather around the stomata driven by the Laplace gradient and be absorbed by the fleshy stem, making it survive in harsh environments . Unfortunately, most of the artificial AWH materials based on hydrogels or metal–organic frameworks (MOFs) arguably have insufficient vapor liquefaction ability. , Although researchers have incorporated hygroscopic salts into these materials to enhance their water adsorption capacity under ambient conditions, the strong affinity of hygroscopic salts for water molecules in turn leads to a reduced water release/production efficiency. , For example, Li et al reported a PAM-based hydrogel containing calcium chloride and carbon nanotubes with a maximum water adsorption capacity of 2.05 g g –1 and a low desorption efficiency of 55% . The trade-off between water uptake (under low-mediate humidity) and water release efficiency under ambient conditions limits the practical applications of artificial AWH materials.…”
Section: Introductionmentioning
confidence: 99%